Kinetics and Mechanism of oxidation of Isopropanol by Chloramine-T - Mehrotra, R.M. (Asian Journal of Chemistry, 2010)
Kinetic studies on the oxidation of isopropanol have been made using chloramine-T as an oxidising agent in acidic medium. The reaction showed first order dependence with respect to chloramine-T and hydrogen ion concentration and the rate was found to be independent of the isopropanol concentration. No effect of ionic strength was evident. A plausible mechanism consistent with the experimental results has been proposed. The various Arrhenius parameters have also been computed.